Перевод как истолкование (Hor. Carm. 3, 30) [Valerij Durov. Translation as Interpreting (Hor. Carm. 3. 30)] - Дуров, В. С. (Hyperboreus, 2011)
The author examines Russian translations of Horace’s Carm. 3, 30 focusing on different interpretations of the Latin text.